Sustainable urban development - the need for a South African rating tool for sustainable precinct developments - Potgieter, Melissa (Department of Construction Economics and Management, 2017)
Globally, urban sustainability is shifting its focus from individual building to sustainability at precinct, neighbourhood and community levels. This dissertation aims to determine whether the South African urban development industry has a need for the introduction and incorporation of a precinct level urban sustainability rating tool. This dissertation employs a literature review and single case study approach to define precinct level urban sustainability, to explore existing sustainability initiatives and to investigate the expected impacts of a South African precinct level urban sustainability rating tool. The research finds that while there ha been interest in precinct level sustainability from the private sector and some leading municipalities, precinct level sustainability runs the risks of becoming nothing more than a political catch-phrase and of becoming stuck in an ongoing cycle of planning, especially from a national regulatory point of view. It is expected that the introduction of a South African precinct level sustainability rating tool will mitigate this situation by providing motivation for the adoption of, and a clear guideline for the physical implementation of, wider sustainability principles and objectives.